2012
DOI: 10.1111/j.1467-9213.2012.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Rejecting The Publicity Condition: The Inevitability of Esoteric Morality

Abstract: It is often thought that some version of what is generally called the publicity condition is a reasonable requirement to impose on moral theories. In this article, after formulating and distinguishing three versions of the publicity condition, I argue that the arguments typically used to defend them are unsuccessful and, moreover, that even in its most plausible version, the publicity condition ought to be rejected as both question‐begging and unreasonably demanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fromtheperspectiveofethicaltheoryonthesubjectofsecrecy,therearetwooppositeframeworks toconsider:theutilitarianandthedeontological.Anextremeposition,expressedbySidgwick(1874), basically states that promoting rules for public acceptance does not eliminate the possibility of permissiblesecrecy.Amongthecontemporarythinkers, Eggleston(2013)goesevenfurther,claiming thatthepublicityconditionforpublicpolicyisexcessivelydemandingandquestion-begging. Kant(1795)representsanotherextremeclaimingthat"Allactionsrelatingtotherightofother humanbeingsarewrongiftheirmaximisincompatiblewithpublicity".Itisobviousthatsabotage requiresstealthanddeception.ShouldwetakeitforgrantedthatKantwouldobviouslyrejectit?…”
Section: Secrecymentioning
confidence: 99%
“…Fromtheperspectiveofethicaltheoryonthesubjectofsecrecy,therearetwooppositeframeworks toconsider:theutilitarianandthedeontological.Anextremeposition,expressedbySidgwick(1874), basically states that promoting rules for public acceptance does not eliminate the possibility of permissiblesecrecy.Amongthecontemporarythinkers, Eggleston(2013)goesevenfurther,claiming thatthepublicityconditionforpublicpolicyisexcessivelydemandingandquestion-begging. Kant(1795)representsanotherextremeclaimingthat"Allactionsrelatingtotherightofother humanbeingsarewrongiftheirmaximisincompatiblewithpublicity".Itisobviousthatsabotage requiresstealthanddeception.ShouldwetakeitforgrantedthatKantwouldobviouslyrejectit?…”
Section: Secrecymentioning
confidence: 99%
“…They claim that utilitarianism is self-effacing: it requires us not to accept utilitarianism. This allows them to accept 3 whilst arguing that it is no mark against utilitarianism: whatever attitudes the agent who accepts utilitarianism has towards their projects are not required by utilitarianism as a theory (Eggleston, 2013;Lazari-Radek & Singer, 2010;Parfit, 1984, Chap. 1;Railton 1984).…”
mentioning
confidence: 99%
“…It has been observed that there is a parallel "paradox of consequentialism," that is, that thinking in consequentialist terms can prevent agents from producing the best consequences. SeeWilliams (1973),Stocker (1976),Railton (1984),Wiland (2007), andEggleston (2013b). One response to this worry has been to argue that even if it would be a bad idea for agents to believe in or try to follow a consequentialist theory, this does not mean that the theory is incorrect.…”
mentioning
confidence: 99%
“…22Parfit (1984: Sect. 18) andEggleston (2013b).dietz Journal of Moral Philosophy 18 (2021) 387-411 Downloaded from Brill.com08/23/2021 03:06:30AM via free access…”
mentioning
confidence: 99%